COMPARATIVE CLINICAL STUDY TO EVALUATE THE EFFECT OF ‘PHALA GHRIT’- ORAL &UTTAR VASTIIN ‘VANDHYATWA’ W.S.R. TO FEMALE INFERTILITY - Chinchalkar Shital; Londhe Deepak; B.Pushpalatha; Sharma Sushila (International Journal of Applied Ayurved Research, 2016)
Motherhood is the cherished desire deep down in the heart of every woman. The desire for offspring in every woman is as synonymous with motherhood as it adds a new meaning to her life and existence. Infertility has been long standing problem since ancient period but it is most burning issue nowadays because of improper lifestyle. Childlessness may be a tragedy to the married woman, and can be a cause of marital upset as well as of personal unhappiness and ill health.In Ayurveda Infertility is termed as Vandhyatwa. Ayurveda may give a promis-ing hand to cure this disease. As the subject is discussed in Ayurveda, it becomes necessary to study, understand and prove them particularly in light of modern scientific parameters in the present era. So the field of research in the Vandhyatwa opens broad scope for a worker, hence this topic requires proper thought & orientation in implementation of Ayurvedic treatment of success in aimed target of attaining twinkle in the eye of childless women.In Samprapti, the main Adhisthana of the Vandhyatwa is Yoni. Vata Dosha is the governing factor of the whole reproductive physiology therefore any vitiation in Vata will certainly affect the fertility. In Ayurveda, Sneha and Vasti said to be the best treatment for Vata. Hence Uttar Vasti is se-lected as procedure. Considering all these points, in present study the Ghrita preparation was selected for oral medicine and Uttar Vasti. Clinical study was completed on clinically diag-nosed 30 patients of female infertility in P.G. department of Prasuti and Striroga, National Institute of Ayurveda at Jaipur (Raj.).The patients were divided into two groups of 15 pa-tients each with the aim to see the effect of Phala Ghrit, to compare the efficacy of Uttar Vasti & oral therapy in female infertility.